Activated carbon coupled with citric acid in enhancing the remediation of Pb-Contaminated soil by electrokinetic method. (25th July 2021) - Xie, Ning; Chen, Zhen; Wang, Haiming; You, Changfu
Abstract: Soil contaminated by heavy metals has received widespread attention, and the efficient removal of heavy metals remains a challenge. A novel process for enhancing the electrokinetic (EK) performance to remediate the Pb-contaminated soil was proposed by coupling the activated carbon (AC) and citric acid (CA). The synergetic effect of AC and CA was found to significantly improve the Pb removal efficiency by EK method. The Pb removal efficiency was only about 4% after 480 h treatment in the traditional EK cell, and it was improved greatly to 15% and 58% after adding CA and CA + AC, respectively. The introduction of CA caused more soluble Pb complexes to be formed through carboxyl and hydroxyl groups, which accelerated the dissolution and desorption of Pb in soil. However, with only CA addition in the EK cell, a high pH of 13 was observed near the cathode causing the metal precipitation near the cathode, thereby blocking soil pores and hindering the remediation process. With the assistance of AC, a more uniform pH distribution was developed and the pH in the whole EK cell was maintained below 10, which was beneficial for the transportation of Pb. Furthermore, the removed Pb was retained in the AC without generating Pb-containing wastewater to realize the cleaner production of the remediation process. In addition, this study developed tubular electrodes without additional electrolytic cells, which largely simplified the EK remediation system and can be more easily deployed in the field test for real-world application. Graphical abstract: Image 1 Highlights: Citric acid and activated carbon were used to enhance the EK remediation of Pb. pH was more uniform in the soil after adding citric acid and activated carbon. Pb removal efficiency increased from 4% to 58% by the enhanced EK method.